Histological and immunohistochemical study of the effect of liraglutide in experimental model of non-alcoholic fatty liver disease. Issue 1 (31st December 2023) - Salah Nour, Mai; Sakara, Zeinab Abd El-Hay; Hasanin, Nawal Awad; Hamed, Shereen Mohamed
ABSTRACT: Nonalcoholic fatty liver disease (NAFLD) is known as the accumulation of triglycerides in liver without alcohol consumption. Liraglutide is an analogue of glucagon-like peptide-1 hormone (GLP-1). It is known to decrease blood glucose, body weight and food intake. The present study is designed to study the effect of liraglutide on the experimental model of NAFLD. Thirty-six adult male albino rats were divided into three groups. Group I was the control group. Group II (FLD group) received a high-fat fructose diet for 16 weeks. Group III (FLD + Lira) received high-fat fructose diet daily for 16 weeks and were injected with Liraglutide intraperitoneally at a dose of 0.6 mg/kg/day in the last 4 weeks. Liver sections were prepared for histological, immunohistochemical and Western blot study of alpha smooth muscle actin and beclin 1. Group II showed macrovesicular and microvesicular steatosis, a strong positive immunoreaction of αSMA (alpha smooth muscle actin) and a weak positive immunoreaction of beclin 1. Group III showed a much better histological picture and a moderate positive immunoreaction of αSMA and beclin 1. In conclusion, liraglutide could treat NAFLD by improving hepatic steatosis and fibrosis, regulating lipid profile and liver functions, and enhancing autophagy.